In situ Enabling Approaches for Tissue Regeneration: Current Challenges and New Developments - Dias, Juliana R.; Ribeiro, Nilza; Baptista-Silva, Sara; Costa-Pinto, Ana Rita; Alves, Nuno; Oliveira, Ana L. (Frontiers in Bioengineering and Biotechnology, 2020)
In situ tissue regeneration can be defined as the implantation of tissue-specific biomaterials (by itself or in combination with cells and/or biomolecules) at the tissue defect, taking advantage of the surrounding microenvironment as a natural bioreactor. Up to now, the structures used were based on particles or gels. However, with the technological progress, the materials’ manipulation and processing has became possible, mimicking the damaged tissue directly at the defect site. This paper presents a comprehensive review of current and advanced in situ strategies for tissue regeneration. Recent advances to put in practice the in situ regeneration concept have been mainly focused on bioinks and bioprinting techniques rather than the combination of different technologies to make the real in situ regeneration. The limitation of conventional approaches (e.g. stem cell recruitment) and their poor mimicking of native tissue are discussed. Advanced strategies such as 3D/4D bioprinting and hybrid approaches are highlighted as they may contribute to overcome the limitations of conventional strategies. The main research challenges and future trends of in situ enabling approaches are discussed in the light of in vitro and in vivo evidence.